National Data Sharing Policy in the Era of Open Science: A Systematic Literature Review - Cahyo Trianggoro; Tupan Tupan (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
Research data sharing activities provide many benefits to the research ecosystem. However, in the Indonesian context, there is a lack of policy in regulating research data sharing mechanisms which makes researchers reluctant to undertake the practice of data sharing. Research funders and research institutions play a critical role in developing data-sharing policies. Research related to the policy of research data sharing is important in order to design policies to encourage the practice of research data sharing. A systematic literature review was conducted to see how data-sharing policies were formulated and implemented in various research institutions. The data were taken from Scopus and Dimension indexers using controlled vocabulary. The roles of research institutions and funders as well as policy instruments were analyzed to see patterns that occur between the parties. We examine 23 articles containing data sharing policies. it was found that the funders have the greatest role in determining the design of the data sharing policy. Funders view that research data is an asset in research funded by public funding so that the benefits must be returned to the community. Research institutes play a role as a provider of research infrastructure that contributes to data creation. Meanwhile, researchers as research actors need to provide input in developing data sharing mechanisms and regulating data sensitivity aspects and legal aspects in research data sharing.